A COMPARATIVE ANALYSIS OF THE INITIAL EAST EUROPEAN CENTER EXPERIENCE WITH A WESTERN HIGH-VOLUME CENTER FOR OPEN MINIMALLY INVASIVE PARATHYROIDECTOMY (OMIP) AS TREATMENT OF PRIMARY HYPERPARATHYROIDISM - Neagoe, R.M. (Acta Endocrinol (Buchar), 2016)
OBJECTIVE: To compare results of treatment of primary hyperparathyroidism (PHPT) in two teaching hospitals (eastern and western Europe) and to establish conclusions regarding quality of surgery for PHPT in Romania. METHODS: We reviewed two prospectively collected databases of patients submitted to open minimally invasive parathyroidectomy (OMIP) for symptomatic PHPT in two centers from Romania and the United Kingdom (UK). We included patients with biochemically proven PHPT and positive pre-operative localization studies. We excluded patients with negative localization studies, suspected multiglandular disease, concomitant thyroid disorders and chronic renal failure. RESULTS: 60 patients were included, 27 in group A (Romanian cohort) and 33 in group B (UK cohort). We noted significant differences between groups in pre-operative serum calcium and phosphorus levels (p<0.5). There were no differences between groups regarding the presence of symptoms; in group A we had significantly more patients with renal calculi history (p=0.02), digestive symptoms (p=0.006) and osteitis fibrosa cystica (p=0.01). Two patients from the UK group had lithium associated hyperparathyroidism and 2 patients had genetic disease. Intraoperative parathyroid hormone measurement (ioPTH) was available only for group B and frozen sections were selectively used in both groups. Both the adenoma size and weights were significantly higher in group A. The median operative time was significantly longer in Romanian group (p=0.001); in this group we noted the single conversion to traditional cervicotomy (3.7%) from all studied patients. In group A we noted two patients (7.4%) with failed parathyroidectomy and persistent PHPT; the cure rate was 92.5% for Romanian group and 97% for the UK group. CONCLUSIONS: OMIP can be performed safe with a high cure rate in “small” volume endocrine centres with results comparable to western experienced endocrine centres. Romanian patients presented with more severe PHPT with more frequent end-organ damage, due probably to late diagnosis.